Village Fund Realization, Leadership Capacity, and Geographical Barriers: Evidence from 1,841 Villages in Central Sulawesi, Indonesia - Annisa Nabila Febryana; Tenripada Tenripada; Ni Made Suwitri Parwati; Andi Chairil Furqan (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to analyze the influence of the realization of village funds, the capacity of the village head, and the geographical barriers on the performance of the village government. Based on 1.841 villages in Central Sulawesi using Fixed Effect Regression, it was found that the realization of village funds and the education level of the village head had a significant positive influence on the performance of the village government, while the geographical barriers had a significant negative influence on the performance of the village government. Therefore, it can be concluded that optimizing the use of village funds, increasing human resource capacity, and reducing geographical barriers are important factors in encouraging the effectiveness of village governance. From the findings, it is hoped that it will be an encouragement for the government to improve village development through increasing the realization of targeted village funds, paying attention to certain aspects in the recruitment of village heads, and the use of special strategies to overcome performance gaps in villages far from the city/district center